Colitis Cystica Profunda Complicated by Complete Colorectal Obstruction - Hugh James Freeman (Canadian Journal of Gastroenterology)
An unusual presentation of colitis cystica profunda was seen in a 39-year-old male with a complete colonic obstruction due to an intussception with a rectosigmoid inflammatory mass. The patient had apparent antecedent distal ulcerative colitis and management included subtotal colectomy. Removal of the rectosigmoid mass produced a satisfactory clinical result with no colonoscopic or histological evidence of recurrent disease in the subsequent decade. Although rare, this entity should be considered during the evaluation of any inflammatory process involving the distal colon, especially if an inflammatory polypoid colonic mass is present or a mucinous adenocarcinoma is suspected.